Growth of calcium phosphate using chemically treated titanium oxide nanotubes - Escada, A. L.A. [UNESP]; MacHado, J. P.B.; Schneider, S. G.; Nakazato, Roberto Zenhei [UNESP]; Claro, A.P.R. Alves [UNESP] (Trans Tech Publications, 2012)
Many materials with different surfaces have been developed for dental and orthopedics implants. Among the various materials for implants, titanium and bioactive ones such as calcium phosphates and hydroxyapatite, are widely used clinically. When these materials are inserted into bone several biological reactions occur. Thes processes can be associated with surface properties (topography, roughness and surface energy). In this work, ingots were obtained from titanium and molybdenum by using an arc-melting furnace. They were submitted to heat treatment at 1100°C for one hour, cooled in water and cold worked by swaging. Titanium nanotubes were fabricated on the surface of Ti-7,5Mo alloy by anodization, and then treated with NaOH solution to make them bioactive, to induce growth of calcium phosphate in a simulated body fluid. . It is shown that the presence of titanium nanotubes induces the growth of a sodium titanate nanolayer. During the subsequent in-vitro immersion in a simulated body fluid, the sodium titanate nanolayer induced the nucleation and growth of nano-dimensioned calcium phosphate. These titanium nanotubes can be useful as a well-adhered bioactive surface layer on Ti implant metals for orthopedic and dental implants. © (2011) Trans Tech Publications, Switzerland.
Keywords: Calcium Phosphate; Nanotubes TiO 2; Titanium alloys